The power of position : Beijing University, intellectuals, and Chinese political culture, 1898-1929 - Weston, Timothy B., 1964- (Berkeley series in interdisciplinary studies of China ;, 2004)
Throughout the twentieth century, Beijing University (or Beida) has been at the center of China's greatest political and cultural upheavals--from the May Fourth Movement of 1919 to the Cultural Revolution of the 1960s to the tragic events in Tiananmen Square in 1989. Why this should be--how Beida's historical importance has come to transcend that of a mere institution of higher learning--is a question at the heart of this book. A study of intellectuals and political culture during the past century's tumultuous early decades, The Power of Position is the first to focus on Beida, China's oldest an.